Application of the Case Study Method in Medical Education - Korniichuk, O. Y.; Bambyzov, L. M.; Kosenko, V. M.; Spaska, A. M.; Tsekhmister, Y. V.; Бамбизов, Леонід Михайлович (My University, 2021)
Reducing the gap between professional opportunities of graduates of medical education institutions and needs of patients is the priority of medical education. The introduction of interactive methods, in particular the case study method, can help solve this problem. The aim of this study was to investigate how the application of the case method in medical education affects the learning outcomes of students and acquisition of practical experience. Case method was used to identify its impact on the acquisition of practical skills, abilities and clinical experience by future physicians. Students’ opinions on the effectiveness of the case method in gaining practical experience were surveyed. The study showed that the case method helped students find solutions required by clinical situations, as they used not only theoretical knowledge, but also acquired practical skills and clinical experience. The case method also increases students’ confidence in their professional abilities. This experimental study proved the high efficiency of using the case method in medical education to gain practical experience by students in the education institution. It can be useful for scholars and educators who are looking for, developing and implementing effective teaching methods that allow students to acquire the necessary competencies.
Keywords: teaching methods; clinical case; clinical situation; medical experience; interactive method